Repurposing fertilizer subsidies in India: An economywide modelling analysis - Devi, Asha; Praveen, K. V.; Sharma, Kriti; Pal, Barun Deb; Singh, Alka; Barman, Subrata; Reddy, K. R.; Hanji, Shreya; Rao, Ch. Srinivasa (Indian Council of Agricultural Research, 2025)
Between 1980 and 2023-pushed by green revolution technology and fertilizer subsidy policy-fertilizer consumption in India increased from 31.95 kg/ha to 136.05 kg/ha {FAI 2024). The fiscal burden of fertilizer subsidies in India has surged dramatically, increasing from INR 505 crores in 1980/1981 to INR 2,25,220 crores in 2022/2023 ( ibid). As of 2022/2023, the budgetary allocation for fertilizer subsidy was 1.02 percent of India's gross value added (GVA). Fertilizer subsidies have led to greater price increases for phosphorus and potassium fertilizers than for urea, making urea the preferred choice among farmers. This consequent overreliance on urea has created significant imbalances in soil nutrient composition, and subsidized urea is also often diverted to other industries undermining its intended benefit for the agricultural sector.